Control of Transcriptional Elongation - Kwak, Hojoong (2013)
Elongation is becoming increasingly recognized as a critically controlled step in transcriptional regulation. While traditional genetic and biochemical studies have identified major players of transcriptional elongation, our understanding of the importance and roles of these factors is evolving rapidly through the recent advances in genome-wide and single-molecule technologies. Here we focus on how elongation can modulate the transcriptional outcome through the rate-liming step of RNA polymerase II pausing near promoters, and how the participating factors were identified. Among the factors we describe are NELF and DSIF, the pausing factors, and P-TEFb, the key player in pause release. We also describe non-exclusive models for how pausing is achieved by making use of high resolution genome-wide mapping of paused Pol II relative to promoter elements and the first nucleosome. We also discuss Pol II elongation through the bodies of genes and the roles of FACT and Spt6, the factors that allow Pol II to move through nucleosomes.